Minning land use/land cover Information and Changing Landscape Pattern Analysis using Remote Sensing Aided machine Learning Techniques - Mishra, Varun Narayan (IIT(BHU), Varanasi, 2018)
Abstract is available in the attachment
This Thesis submitted by PhD Scholar IIT(BHU), Varanasi. & supervised by Rajendra Prasad.
Keywords: Minning Land; Landscape; Remote